Rancang Bangun Dashboard Analisis Penjualan Berbasis Web Sebagai Pendukung Monitoring Operasional dan Evaluasi Keuangan - Azra Daiva Tirtany; Farizi Ilham; A. Zakin Munif; Prasetio Wicaksono (CV. Shofanah Media Berkah, 2026)
Operational management at LPG gas stations and drinking water depots generally still faces challenges in manually recording transactions. This situation causes data fragmentation between subsidized and unsubsidized gas sales and mineral water products, resulting in slow data collection and accurate financial assessments. This study aims to design and build a web-based sales analytics dashboard that can integrate all transaction data into a single, centralized platform. The development methodology used is the Waterfall method, which includes the steps of requirements analysis, system design, coding, and testing. The proposed system has integrated features in the form of sales graph visualization, inventory management, periodic financial reports, and the ability to forecast sales and growth scenarios of 10 percent. Functional testing shows that all modules operate according to user requirements. With this system, depot owners can monitor performance in real time and make strategic decisions based on organized and accurate data.